Wideband back-cover antenna design using dual characteristic modes with high isolation for 5G MIMO smartphone - Hu, Wei (2022)
A novel method of designing a wideband high-isolated dual-antenna pair using dual-characteristic modes (CMs) is presented for fifth-generation (5G) multiple-input multiple-output (MIMO) smartphone applications. A set of orthogonal CMs resonating from the square-loop slot is first introduced and works for the lower band. Then, another set of orthogonal CMs resonating from the edge branches is introduced with a shared compact radiator and works for the higher band. In combination with two sets of degenerated CMs and a capacitive coupling feeding structure, the proposed dual-antenna pair achieves a broad impedance bandwidth and high isolation without the need for any external decoupling structures. Based on this dual-antenna pair, an 8times 8 MIMO array is developed and integrated into the back cover of a smartphone, which realizes zero ground clearance on the system circuit board. To verify the design concept, prototypes of the antenna pair and MIMO array were fabricated and measured. It shows that experimental results agree well with the simulation results. More importantly, the presented 8times 8 MIMO array has high isolation of more than 20 dB is achieved across the operating band of 3.3-3.8 GHz.